SH3-binding glutamic acid rich-deficiency augments apoptosis in neonatal rat cardiomyocytes - Deshpande, Anushka; Borlepawar, Ankush; Rosskopf, Alexandra; Frank, Derk; Frey, Norbert; Rangrez, Ashraf Yusuf (International journal of molecular sciences, 2021)
Congenital heart disease (CHD) is one of the most common birth defects in humans, present in around 40% of newborns with Down’s syndrome (DS). The SH3 domain-binding glutamic acid-rich (SH3BGR) gene, which maps to the DS region, belongs to a gene family encoding a cluster of small thioredoxin-like proteins sharing SH3 domains. Although its expression is confined to the cardiac and skeletal muscle, the physiological role of SH3BGR in the heart is poorly understood. Interestingly, we observed a significant upregulation of SH3BGR in failing hearts of mice and human patients with hypertrophic cardiomyopathy. Along these lines, the overexpression of SH3BGR exhibited a significant increase in the expression of hypertrophic markers (Nppa and Nppb) and increased cell surface area in neonatal rat ventricular cardiomyocytes (NRVCMs), whereas its knockdown attenuated cellular hypertrophy. Mechanistically, using serum response factor (SRF) response element-driven luciferase assays in the presence or the absence of RhoA or its inhibitor, we found that the pro-hypertrophic effects of SH3BGR are mediated via the RhoA-SRF axis. Furthermore, SH3BGR knockdown resulted in the induction of apoptosis and reduced cell viability in NRVCMs via apoptotic Hippo-YAP signaling. Taking these results together, we here show that SH3BGR is vital for maintaining cytoskeletal integrity and cellular viability in NRVCMs through its modulation of the SRF/YAP signaling pathways.
Gesehen am 07.12.2021